TNF‐derived peptides inhibit tumour growth and metastasis through cytolytic effects on tumour lymphatics. (3rd July 2019) - Lu, W.; Wang, Y.; Zhang, Q.; Owen, S.; Green, M.; Ni, T.; Edwards, M.; Li, Y.; Zhang, L.; Harris, A.; Li, J‐L.; Jackson, D. G.; et al.
Summary: Tumour necrosis factor (TNF) is a multi‐functional cytokine with profound and diverse effects on physiology and pathology. Identifying the molecular determinants underlying the functions and pathogenic effects of TNF is key to understanding its mechanisms of action and identifying new therapeutic opportunities based on this important molecule. Previously, we showed that some evolutionarily conserved peptides derived from TNF could induce cell death (e.g. apoptosis and/or necrosis), a feature of immune defence mechanisms shared by many vertebrates. In this study, we demonstrated that necrosis‐inducing peptide P16 kills human glioblastoma cancer cells and primary human hepatoma or renal cancer cells isolated from patients who had not responded to standard treatments. Importantly, we show that the necrosis‐inducing peptide P1516 significantly improves survival by inhibiting tumour metastasis in a 4T1 breast cancer syngeneic graft mouse model. Because the lymphatic system is an important metastatic route in many cancers, we also tested the effect of TNF‐derived peptides on monolayers of primary human lymphatic endothelial cells (hDLEC) and found that they increased junctional permeability by inducing cytoskeletal reorganization, gap junction formation and cell death. Transmission electron microscopy imaging evidence, structural analysis and in‐vitro liposome leakage experiments strongly suggest that this killing is due to the cytolytic nature of these peptides. P1516 provides another example of a pro‐cytotoxic TNF peptide that probably functions as a cryptic necrotic factor released by TNF degradation. Its ability to inhibit tumour metastasis and improve survival may form the basis of a novel approach to cancer therapy. Abstract : TNF stimulates cell growth while peptide P1516 derived from TNF induces necrotic cell death. Lymphatic endothelial cells are especially sensitive to P1516‐induced cell death, resulting in collapse of cellular skeletal structure as shown in the figure. In In Vivo experiments, the damage of lymphatic vessels around tumour by P1516 might be the reason to inhibit the metastasis and therefore to increase the survival rate.